2010
DOI: 10.46989/001c.20577
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Genotyping of Vibrio ordalii: A Comparison of Different Methods

Abstract: As from January 2010 The Israeli Journal of Aquaculture-Bamidgeh (IJA) will be published exclusively as an on-line Open Access (OA) quarterly accessible by all AquacultureHub (http://www.aquaculturehub.org) members and registered individuals and institutions. Please visit our website (http://siamb.org.il) for free registration form, further information and instructions. This transformation from a subscription printed version to an on-line OA journal, aims at supporting the concept that scientific peer-reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Vibrio ordalii, formerly Vibrio anguillarum biovar II (Schiewe et al 1981), is an important causative agent of vibriosis in several salmonid species cultured in the USA, Japan, Australia, New Zealand and Chile (Harrell et al 1976, Ransom et al 1984, Toranzo et al 1997, Colquhoun et al 2004, although it has also been reported as a pathogen for other fish species such as gilthead sea bream Sparus aurata in Turkey (Akayli et al 2010). This pathogen is a Gram-negative, motile, rod-shaped bacterium that is fermentative, catalase and oxidase positive, and sensitive to the vibriostatic agent O/129 (Farmer et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio ordalii, formerly Vibrio anguillarum biovar II (Schiewe et al 1981), is an important causative agent of vibriosis in several salmonid species cultured in the USA, Japan, Australia, New Zealand and Chile (Harrell et al 1976, Ransom et al 1984, Toranzo et al 1997, Colquhoun et al 2004, although it has also been reported as a pathogen for other fish species such as gilthead sea bream Sparus aurata in Turkey (Akayli et al 2010). This pathogen is a Gram-negative, motile, rod-shaped bacterium that is fermentative, catalase and oxidase positive, and sensitive to the vibriostatic agent O/129 (Farmer et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Paillard et al recognized that the emergence of vibrios as etiological agents of diseases is likely to increase over the coming years due to ocean warming [9]. Classical vibriosis is generally characterized by lethargic movement of affected fish [10][11][12], the presence of various skin ulcerations [12][13][14][15], rotting fins [14,16,17], and pigmentation of the body [10,13,14,18]. Internal organs appear enlarged, hemorrhagic and congested, particularly the liver, kidney, and spleen [11,12,18].…”
Section: Introductionmentioning
confidence: 99%